Pengaruh Pemberian Kompos Kulit Udang dan Pestisida Nabati Keong Mas Terhadap Kadar Air dan Persentase Serat Kenaf - Rusmini (Jurusan Teknologi Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2020)
Kenaf planting generally uses chemical fertilizers to enhance production although they are harmful to environmental ecosystems. At the same time, agricultural and fishery wastes have been underutilized. Kenaf is environmentally friendly natural fiber-producing plant that can produce diversified products, such as paper, wallcover, car interior, geotextile, soil safer, fiber drain, particle board, and plastic reinforcement as well as biofuel industry raw materials.The objective of this research was to know the water content of kenaf under the provision of organic shrimp fertilizer and natural pesticide of golden snail. The study used a Randomized Block Design with two factors with the first factor compost of shrimp (k) consisting of 3 levels and the second factor was a vegetable pesticide consisting of three levels (p). Each of these studies was repeated as many as 2 replications so that there were 18 treatmentoverall. Variables observed was water content of kenaf stem. The data obtained were analyzed using variance analysis and continued with the smallest real difference test at the 5% test level. The results showed that the best water content was in the combination of the k2p0 treatment of 63.6075%.